Cover Picture: Identification of Cellular MicroRNA Coupling Strand Displacement Polymerization and Nicking‐Endonuclease‐Based Cleavage (ChemPlusChem 12/2015). Issue 12 (19th October 2015) - Miao, Peng; Tang, Yuguo; Zhang, Qi; Bo, Bing; Wang, Jue
Abstract : The cover picture shows the design of a target‐induced recycling amplification method for the detection of cellular microRNA. A combination of strand‐displacement polymerization and nicking‐endonuclease‐mediated cleavage is employed. Intense electrochemical signals are provided by a silver‐nanoparticle‐based solid‐state Ag/AgCl reaction, and ultrahigh sensitivity for microRNA is achieved. More details can be found in the Communication by Peng Miao, Jue Wang, and co‐workers onpage 1712 in Issue 12, 2015 (DOI:10.1002/cplu.201500249 ).